Convenção de Estocolmo sobre poluentes orgânicos persistentes: impactos ambientais, sociais e econômicos associados - Castelo Branco, Jeffer [UNIFESP] (2016)
This master dissertation aims to study the development reasons of an international binding treaty on control of Persistent Organic Pollutants (Convention on POPs), and also to analyze the effectiveness of the Convention in Brazil, including the possibility of civil society to participate in this process, the formulation of the Convention implementation plan and the ability of environmental agencies at acting in this process. In order to allow more detailed analysis of the researched material, as one of the evaluation parameters of the associated environmental, economic and social impacts it was chosen a case study, which was in the end analyzed with the DPSIR model, aiming to understand the complexities and their positive and negative feedback on preventing the resolution of socio-economic and environmental associated impact. The knowledge fragmentation interferes directly in decision-making processes, allowing mankind to develop various poisonous chemicals and to introduce them in its daily lives. In the last six decades, mankind has experienced economic and population growth unprecedented in its history, with a new emerging global society that promotes the spread of new and dangerous environmental contaminants. Structural and governance improvements within the government are essential as well as the efforts to replace the treatment process, whose results are the same dangerous chemical compounds that were intended to treat. Finally, the complex thinking proved itself important, regarding, in particular, the need for effective, transcendent and necessary theory in the process of implementation of the Convention on POPs.